Beyond the formal/informal employment dualism: evaluating individual- and country-level variations in the commonality of quasi-formal employment. Issue 9 (31st May 2021) - Williams, Colin; Krasniqi, Besnik
Abstract : Purpose: To transcend the view of employment as either formal or informal, this paper evaluates the prevalence of quasi-formal employment where formal employers pay formal employees an unreported ("envelope") wage in addition to their formal reported salary. To explain the individual-level variations in quasi-formal employment, the "marginalisation" thesis is evaluated that this practice is more prevalent among vulnerable groups and to explain the country-level variations, and a neo-institutionalist theory is evaluated that it is more prevalent where formal institutional failures lead to an asymmetry between the formal laws and regulations and the unwritten socially shared rules of informal institutions. Design/methodology/approach: To evaluate the individual- and country-level variations in the prevalence of quasi-formal employment, a multi-level logistic regression is provided of data from special 2019 Eurobarometer survey 92.1 involving 11, 793 interviews with employees across 28 European countries (the 27 member states of the European Union and the United Kingdom). Findings: Of the 3.5% of employees (1 in 28) who receive under-reported salaries, the marginalisation thesis is supported that it is largely vulnerable population groups. So too is the neo-institutionalist explanation that quasi-formal employment is more common in countries where the non-alignment of formal and informal institutions is greater, with the formal institutional failings producing this identified as lower levels of economic development, less modernised state bureaucracies and lower levels of taxation and social protection. Practical implications: The policy implication is that tackling quasi-formal employment requires not only enforcement authorities to improve the risk of detection of this illegal wage practice but also governments to change wider macro-level structural conditions. These are outlined. Originality/value: Contemporary new evidence is provided of the prevalence of quasi-formal employment along with how this illegal wage practice can be explained and tackled.